DENOTATIVE AND CONNOTATIVE MEANINGS IN ENGLISH PROVERBS (A SEMANTIC STUDY) - Fannasyta F.R Matindas; Nurmin Samola; Tirza Kumajas (Journal of English Culture, Language, Literature and Education, 2020)
This study aimed at identifying denotative and connotative meaning in English proverbs, in Solomon’s Proverbs in Proverbs 25, 26, and 28, King James Version. This study was conducted in order to explain the patterns of proverb that used on Solomon’s proverbs in Proverbs 25, 26, and 28, King James Version. In conducting this study, descriptive method were used. The data were collected through documentation, the writer spending times in reading and analysing the Solomon’s Proverbs in Proverbs 25, 26, and 28, King James Version and the files that in relation with this research. The data were analyzed by following step of unitization, categorization, explanation and interpretation. The result shows that there are 36 English proverbs that used patterns of proverbs by Mieder which are Better X than Y, Like X like Y, No X without Y, One X doesn’t make Y, If X than Y. It is suggested that understand the denotative and connotative meaning in reading English writing especially English Proverbs should be considered in order to get the real meaning that the author or speaker exactly means. Other researcher may conduct a study about denotative and connotative meaning with different point or object.